A critical discourse analysis of Michelle Obama’s speech on International Women’ s Day 2016 - Nguyễn, Thanh Nga (2020)
This study aims at investigating and figuring out the ideologies embedded in the speech delivered by First Lady of the 44th U.S. president, Barack Obama from 2009 to 2017 on International Women’s Day 2016 in Washington D.C.’s Union Market in front of dozens of adolescent girls in the Let Girls Learn from Critical Discourse Analysis (for short CDA) perspective. In this study, the main dialectical – relational framework provided by Norman Fairclough is used to achieve its objective. According to Fairclough’s CDA framework, the study conducts three major steps. The analysis interprets data in three different levels: text analysis (description), processing analysis (interpretation) and social analysis (explanation). Each above phase can be sub- divided into three categories (experiential, relational, expressive). The conclusion supports her ideology that it is necessary that there be an equality for women in education across the globe, and she therefore calls for the approval and support from all corners of the world. It also confirms the relationship between language and ideology in CDA and suggests some implications in language research and pedagogy.